2013
DOI: 10.1037/a0033852
|View full text |Cite
|
Sign up to set email alerts
|

Monopolizing force? Police legitimacy and public attitudes toward the acceptability of violence.

Abstract: Why do people believe that violence is acceptable? In this paper we study people's normative beliefs about the acceptability of violence to achieve social control (as a substitute for the police, for self-protection and the resolution of disputes) and social change (through violent protests and acts to achieve political goals). Addressing attitudes towards violence among young men from various ethnic minority communities in London, we find that procedural justice is strongly correlated with police legitimacy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
137
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 179 publications
(156 citation statements)
references
References 96 publications
8
137
0
4
Order By: Relevance
“…Those behaviors include deference to police authority during personal interactions (Tyler & Huo, 2002); acceptance of police authority as an alternative to private violence or collective disorder (Jackson, Huq, Bradford & Tyler, 2013); heightened compliance with the law (Jackson, Bradford, Hough, Myhill, Quinton & Tyler, 2012;Tyler, 2006a) and increased willingness to cooperate with the police (Jackson, Bradford, Stanko & Hohl, 2012;Sunshine & Tyler, 2003;Tyler & Fagan, 2008). Accordingly, research on the role of legitimacy in law-related behaviors suggests a not-so-hidden cost to the long-term success of policing efforts if the policies and practices of the police undermine their popular legitimacy.…”
Section: Introductionmentioning
confidence: 99%
“…Those behaviors include deference to police authority during personal interactions (Tyler & Huo, 2002); acceptance of police authority as an alternative to private violence or collective disorder (Jackson, Huq, Bradford & Tyler, 2013); heightened compliance with the law (Jackson, Bradford, Hough, Myhill, Quinton & Tyler, 2012;Tyler, 2006a) and increased willingness to cooperate with the police (Jackson, Bradford, Stanko & Hohl, 2012;Sunshine & Tyler, 2003;Tyler & Fagan, 2008). Accordingly, research on the role of legitimacy in law-related behaviors suggests a not-so-hidden cost to the long-term success of policing efforts if the policies and practices of the police undermine their popular legitimacy.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, very little research has experimentally studied the effects of beliefs about police legitimacy on evaluations of civilian resistance toward police; instead, the focus has tended to be on police actions or on motivating civilian cooperation (Thompson & Daniel Lee, 2004;Sunshine & Tyler, 2003;Gerber & Jackson, 2017). A general relationship between high-legitimacy and reduced support for vigilante violence has been demonstrated (Jackson, Huq, Bradford, & Tyler, 2013), but we are unaware of any research on legitimacy modulating evaluations of a wide array of specific civilian reactions to policeespecially not in a manner that corresponds to the way actions are described in police training and policy. The present research provides a first map of lay evaluations of actions that comprehensively span the force categories, and offers insight into how legitimacy affects judgments of both police and civilian violence.…”
mentioning
confidence: 99%
“…Legitimacy is important because it constrains power; study after study has shown that authorities have to act in fair and just ways if they are to be seen to be rightful holders of power by subordinates (Terrill, 2001;McCluskey, 2003). But legitimacy is also important because it reduces the tension between power-holders and subordinates (in the words of Coicaud (2013: 40): the same body of empirical work supports the idea that, when legal authorities act in procedurally just ways, the resulting legitimacy that this engenders in turn encourages people to cooperate with officials, defer to them in moments of crisis, obey the laws they enforce, and accept the state's right to monopolize the use of force in society (Sunshine & Tyler, 2003;Tyler, 2004Tyler, , 2011bTyler & Jackson, 2014;Papachristos et al, 2012;Meares & Tyler, 2014;Mazerolle et al, 2013;Bradford et al, 2014a;Jackson et al, 2012b;Bradford, 2014;Jackson et al, 2013;Hough et al,2013aHough et al, , 2013bNivette, 2014;and Jonathan-Zamir & Weisburd, 2013).…”
mentioning
confidence: 79%